Warlight - Ondaatje, Michael, 1943- (New York : Random House Large Print Publishing, 2018)
In 1945, fourteen-year-old Nathaniel and his older sister Rachel stay behind in London when their parents move to Singapore, leaving them in the care of a figure they suspect might be a criminal.
Keywords: Brothers and sisters -- Fiction; Abandoned children -- Fiction; World War, 1939-1945 -- Fiction; London (England) -- Fiction; Large type books; Historical fiction; Thrillers (Fiction); War fiction